Análise da percepção dos brasileiros sobre aspectos culturais canadenses e dos canadenses sobre aspectos culturais brasileiros - Camello, Natália Spindola (My University, 2018)
One of the barriers to international trade is the cultural differences, which can distance unprepared nations and hinder their intercultural relations. As a result, comparative studies of different cultures are relevant to avoid possible contradictions, since each person perceives, interprets and deduces in different ways. In this context, the present work is focused on the study of intercultural relations between Brazil and Canada, two nations located in the same continent which have close relations in matters such as education, science, technology and innovation. In order to do so, a qualitative research with an exploratory nature was developed, using as a data collection procedure the conduction of interviews in depth, partially structured from scripts with open questions, in order to identify the perception of Brazilians about Canadian culture and of Canadians about Brazilian culture. Through the interviews it was possible to visualize that some cultural factors diverge from Brazilian culture to the Canadian one, mainly uncertainty avoidance, indulgence and factors related to the personality, such as degree of socialization, honesty and civism. The results of this research reinforce the importance of studying different cultures, especially the one which the contact will be made, in order to make those relations more efficient and solid.(sic)
Uma das barreiras ao comércio internacional são as diferenças culturais, as quais podem distanciar nações despreparadas e dificultar suas relações interculturais. Em função disso, estudos comparativos de diferentes culturas são relevantes para evitar possíveis contradições, uma vez que cada pessoa percebe, interpreta e deduz de formas distintas. Nesse contexto, o presente trabalho teve como foco o estudo das relações interculturais entre Brasil e Canadá, sendo essas duas nações situadas no mesmo continente e que possuem relações estreitas em temas como educação, ciência, tecnologia e inovação. Para tanto, foi desenvolvida uma pesquisa de natureza qualitativa de caráter exploratório, utilizando como procedimento de coleta de dados a realização de entrevistas em profundidade parcialmente estruturadas a partir de roteiros com questões abertas, com o intuito de identificar a percepção dos brasileiros sobre a cultura canadense e dos canadenses sobre a cultura brasileira. Por meio das entrevistas foi possível visualizar que alguns fatores culturais divergem da cultura brasileira para a canadense, principalmente a aversão à incerteza, a indulgência e fatores referentes à personalidade, como o grau de socialização, honestidade e civismo. Os resultados da pesquisa reforçaram a importância do estudo das diferentes culturas, sobretudo daquela com a qual se fará contato, a fim de tornar as relações mais eficientes e sólidas.(sic)
Keywords: Cultura; Brasil - Aspectos culturais - Canadá; Relações culturais